An investigation of delisting of the Company from the Zimbabwe Stock Exchange and its effects: A Case of The Cotton Company Of Zimbabwe Limited - Mazengera, Paul (Midlands State University, 2017)
The study investigates the effects of delisting of The Cotton Company of Zimbabwe from the Zimbabwe Stock Exchange and its effects. The study analyses the causes of the delisting of the Cotton Company of Zimbabwe from the Zimbabwe Stock Exchange, the effects of delisting to the company, determinants of share prices and also on relisting and its effects to the company. Primary data was used in this research. The literature regarding the causes, effects of delisting, share prices determinants and relisting was established from various authors. The researcher used case study method making use of 40 questionnaires supplemented by follow-up face to face interviews done by four top managers of the company. The data was analyzed using percentages and presented using statistical tables, pie charts and graphs. A population of 66 and a sample of 40 respondents were used in this research. The study shows that involuntary delisting from the stock exchange has a negative effect to the company and was caused by failure of the company to file its financial results with ZSE within 90 days after its financial year end. The researcher recommended that the company should produce its financial statements in time in order to relists its shares.